1995
DOI: 10.1002/ptr.2650090609
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of korean plant extracts for potential phytotherapeutic agents against B‐virus hepatitis

Abstract: The present study was undertaken to identify potential phytotherapeutic agents among the aqueous extracts of 151 herbal medicinal plants of Korea. Extracts were assayed for (1) binding potency to hepatitis B-virus surface antigen (HBsAg), and (2) inhibition of serum hepatitis B-virus DNA polymerase activity. Of the 151 aqueous plant extracts tested, 33 demonstrated a positive precipitation reaction with HBsAg' serum, and 15 of these specifically bound HBsAg in serum as well as recombinant HBsAg (Hepavax@). Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…New scientifi c strategies for the evaluation of natural products with biological activity require the implementation of large-scale screening programs. It has been suggested that aqueous and ethanolic extracts from plants used in allopathic medicine are potential sources of biological active agents (4,21). Furthermore, the selection of crude plant extracts for screening programs has the potential of being more successful in its initial steps than the screening of pure compound isolated from natural products (5,13).…”
Section: Resultsmentioning
confidence: 99%
“…New scientifi c strategies for the evaluation of natural products with biological activity require the implementation of large-scale screening programs. It has been suggested that aqueous and ethanolic extracts from plants used in allopathic medicine are potential sources of biological active agents (4,21). Furthermore, the selection of crude plant extracts for screening programs has the potential of being more successful in its initial steps than the screening of pure compound isolated from natural products (5,13).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the aqueous and ethanolic extracts from plants used in allopathic medicine are potential source of antiviral, antitumoral and antimicrobial agents (Chung et al, 1995).C. halicacabum possesses various phytochemicals and active biomolecules, which play a major role in the treatment of cancer.…”
Section: B Medicinal Properties Of Cardiospermum Halicacabummentioning
confidence: 99%
“…The timber is widely used for general construction and carpentry in many European countries. It has been suggested that aqueous and ethanolic extracts from plants used in allopathic medicine are potential sources of antiviral, anti tumoural and antimicrobial agents 6 .…”
Section: Issn: 0975-8232mentioning
confidence: 99%
“…The animals were divided into 5 groups (N=6). All the groups were injected with DAL cells (1x10 6 cells/mouse) intraperitoneally except normal group. This was taken as day 0.…”
Section: Treatment Schedulementioning
confidence: 99%